Lexical language-related episodes in pair and small group work - Garcia Mayo, Maria del Pilar; Zeitler, Nora (International Journal of English Studies, 2017)
The present study investigates whether learner set up in interaction, namely in pairs or small groups, influences the frequency and outcome of lexical language-related episodes (LREs) and L2 vocabulary learning. Thirty Spanish English as a foreign language (EFL) university learners took part in the study. They worked in four groups and seven pairs on the same collaborative writing task. Research was carried out on the course of five weeks as a pre- and post- vocabulary task and an individual writing task were administered to assess vocabulary learning and retention. The quantitative analysis of the data showed that there was no significant difference between the performance of pairs and groups, although the latter produced slightly more lexical LREs than pairs and were able to solve most of them correctly. However, from a qualitative point of view, the findings suggest that small group work leads to slightly better results than pair work as the different members obtain benefits from their peers’ linguistic knowledge.